1996
DOI: 10.1016/0014-5793(96)00433-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential display PCR reveals increased expression of 2′,3′‐cyclic nucleotide 3′‐phosphodiesterase by lithium

Abstract: Differential display PCR was used to study the effects of lithium on gene expression. Four candidate genes were isolated and verified by Northern hybridization after 1 week treatment of C6 glioma cells with therapeutically relevant concentrations of LiCI (1 mM). Sequencing analysis revealed three previously unidentified cDNA fragments in addition to a sequence with 99% homology with the cDNA for 2',3'-cyclic nucleotide 3'-phosphodiesterase type II (CNPasell). Since CNPaselI is important in myelinogenesis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…33,34 Additionally, the method of differential display holds great promise as a method capable of distinguishing drug-induced alterations in the expression of specific genes, and the first study with lithium using this method identified 2Ј,3Ј-cyclic nucleotide 3Ј-phosphodiesterase, an enzyme potentially involved in neuronal growth and repair, as being up-regulated after lithium treatment. 143 Overall, although a variety of effects of lithium on mRNA and protein levels have been reported, there is not yet a consensus about which of these may be of primary importance in the therapeutic response, and the mechanisms accounting for these changes caused by lithium have not been identified. At present these findings are most useful as leads for further investigations aimed at identifying the critical affected products, as well as for confirming that lithium clearly does have selective modulatory influences on neuronal gene expression and protein concentrations.…”
Section: Transcription Factors Gene Expression and Protein Levelsmentioning
confidence: 99%
“…33,34 Additionally, the method of differential display holds great promise as a method capable of distinguishing drug-induced alterations in the expression of specific genes, and the first study with lithium using this method identified 2Ј,3Ј-cyclic nucleotide 3Ј-phosphodiesterase, an enzyme potentially involved in neuronal growth and repair, as being up-regulated after lithium treatment. 143 Overall, although a variety of effects of lithium on mRNA and protein levels have been reported, there is not yet a consensus about which of these may be of primary importance in the therapeutic response, and the mechanisms accounting for these changes caused by lithium have not been identified. At present these findings are most useful as leads for further investigations aimed at identifying the critical affected products, as well as for confirming that lithium clearly does have selective modulatory influences on neuronal gene expression and protein concentrations.…”
Section: Transcription Factors Gene Expression and Protein Levelsmentioning
confidence: 99%
“…These novel lithium-regulated targets included 2 Ј , 3 Ј -cyclic nucleotide 3 Ј -phosphodiesterase type II (Wang and Young 1996), polyomavirus enhancer-binding protein 2 ␤ , nitrogen permease regulator 2 (Wang et al 1999), aldolase A (Hua et al 2000), and diphosphoinositol polyphosphate phosphohydrolase II (Hua et al 2001). Unexpectedly, during the course of experiments amplifying the 5 Ј end of a putative lithium-regulated ddPCR fragment, we isolated another cDNA clone, a homolog of human/mouse transmembrane-4-superfamily (TM4SF) protein, CD151.…”
mentioning
confidence: 99%
“…One study revealed upregulation of 2Ј,3Ј-cyclic nucleotide 3Ј-phosphodiesterase type II in rat C6 glioma cells incubated with 1 mM of lithium for one week (Wang and Young 1996). In other studies, altered mRNA levels of the transcription factor polyomavirus enhancer-binding protein 2␤ , nitrogen permease regulator 2 (Wang et al 1999) and aldolase A (Hua et al 2000) were reported in rat frontal cortex following chronic lithium administration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, diverse effects of lithium on several gene transcripts have been described in rat brain and cultured cell models; these transcripts include those for c-fos (Miller and Mathe 1997), G protein ␣ -subunits (Colin et al 1991;Li et al 1993), adenylyl cyclases (Colin et al 1991), dopamine receptors (Dziedzicka-Wasylewska and Wedzony 1996), neuropeptides (Sivam et al 1988(Sivam et al , 1989, and other cellular regulatory proteins (Wang and Young 1996;Feinstein 1998;Shamir et al 1998;Chen and Chuang 1999;Hua et al 2000). To gain a more complete picture of lithium-regulated changes in gene expression, we used differential display polymerase chain reaction (ddPCR), an mRNA-based screening technique to search for candidate genes whose expression is influenced by chronic lithium administration (Hua et al 2000).…”
mentioning
confidence: 99%